2012
DOI: 10.1111/j.1542-4758.2011.00635.x
|View full text |Cite
|
Sign up to set email alerts
|

IL‐6 is an independent risk factor for resistance to erythropoiesis‐stimulating agents in hemodialysis patients without iron deficiency

Abstract: Anemia is a common complication in dialysis patients because of their relative erythropoietin deficiency. Despite treatment with erythropoiesis-stimulating agents (ESAs), some patients experienced ESA hyporesponsiveness. We evaluated the clinical and laboratory factors that affect ESA hyporesponsiveness and investigated the relationships between hepcidin, inflammatory markers, and the iron profiles of hemodialysis patients. Sixty-eight patients receiving hemodialysis at a single institution were evaluated in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 15 publications
2
18
1
Order By: Relevance
“…We did not observe a change in high-sensitivity CRP measurements in our cohort following intervention, but cannot exclude the possibility that improvement in ESA responsiveness was mediated by reduction in low levels of inflammation, which were not detectable by this assay. This is in keeping with data demonstrating improved ESA responsiveness with lower IL-6 levels but without an accompanying significant rise in CRP [38]. …”
Section: Discussionsupporting
confidence: 73%
“…We did not observe a change in high-sensitivity CRP measurements in our cohort following intervention, but cannot exclude the possibility that improvement in ESA responsiveness was mediated by reduction in low levels of inflammation, which were not detectable by this assay. This is in keeping with data demonstrating improved ESA responsiveness with lower IL-6 levels but without an accompanying significant rise in CRP [38]. …”
Section: Discussionsupporting
confidence: 73%
“…Malyszko et al found a positive correlation between hepcidin and CRP levels, whereas others did not. [17][18][19][20][21] In the study by Caliskan et al, 20 serum prohepcidin levels were found to be significantly associated with serum IL-6 levels, however, no significant association was found between prohepcidin and CRP in HD patients. In addition, in our study, serum hepcidin levels were not related to serum CRP levels.…”
mentioning
confidence: 93%
“…HD patients present frequently with high levels of inflammatory markers such as high sensitivity C-reactive protein (hs-CRP), interleukin (IL)-6, tumor necrosis factor-α, neutrophil-to-lymphocyte ratio (NLR) [7], and low levels of serum albumin [8]. Increased levels of pro-inflammatory cytokines reduce the production of erythroid progenitor cells and this contributes to hyporesponsiveness to ESAs and poor treatment outcomes [9,10]. Elevated levels of inflammatory cytokines also contribute to functional iron deficiency.…”
Section: Introductionmentioning
confidence: 99%